Exploring the influence of age, gender, education and computer experience on robot acceptance by older adults - Heerink, M. (2011 6th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2011)
It is generally recognized that non perceptual factors like age, gender, education and computer experience can have a moderating effect on how perception of a technology leads to acceptance of it. In our present research we are exploring the influence of these factors on the acceptance of assistive social robots by older adults. In this short paper we discuss the results of a user study in which a movie of an elderly person using a social assistive robot was shown to older adults. The analysis of the responses give a first indication on if and how these factors relate to the perceptual processes that lead to acceptance.